Auditoría financiera a la Empresa Distribuidora Torres de la ciudad de Loja en el periodo comprendido entre el 01 de enero al 31 de diciembre del 2012. - Bautista Loarte, Jaqueline Maricela (2016)
This thesis entitled " AUDIT FINANCIAL COMPANY DISTRIBUTOR TORRES CITY Loja BY PERIOD FROM 01 JANUARY TO 31 DECEMBER 2012" was conducted with the overall objective : To determine the reasonableness of the Financial Statements Empresa Distribuidora Torres city of Loja, in the period from January 1 to December 31 , which was necessary to meet specific objectives such as: Check the degree of reliability of financial and management information as well as the organization and responsibility accounting area , set the degree of compliance with the laws, statutes and regulations , generally accepted accounting principles and applicable legislation governing the activities of the Distributor , evaluate the internal control system in order to promote improvements in for finding flaws within the resource management of the company and submit a report containing comments , conclusions and recommendations that will enable the business owner to take timely decisions established . Its preparation was necessary to apply a methodology with the same entrepreneurial approach that was developed in stages corresponding where the respective working papers that support the findings that were presented in the audit including the lack of internal control is presented in the audited areas highlights were developed , such as the case where no account is been conducted surprise cash counts for verifying real balances , similarly with respect to accounts receivable timely registration of loans to customers well into the implementation of the financial audit was not carried also noted that Torres Distribuidora not properly presents the financial statements which creates inconsistency in relation to Bank Loan for your duration of 3 years and whose amount is $ 75,000 should be in the long-term liabilities and are reflected in the short term , as well as the variation in income between the statement of financial position showing a value of $ 300,759.96 and $ 106,027.59 Income Statement with a difference of $ 194,732.37 balance that has not been distributed to workers company , therefore the respective programs , questionnaires and procedures Cedulas Analytics whose settings are shown in the Banks account for the difference of $ 29,883.81 between the Statement of Financial Position and Statement Current is conducted the same way Maintenance costs account that Annex Settlement of December a contradiction of $ 3,276.57 with respect to the amount disclosed in the Income Statement , the same approach that led us to Cedulas Summary and making the States was evident financial Statements . Among the conclusions states that Distribuidora Torres does not have a proper control system that allows you to efficiently and effectively perform financial transactions , records of transactions are not performed in a timely manner , making it impossible to rely on the financial information DISTRIBUIDORA “TORRES” generated therefore the balances in the financial statements do not reflect the reality of the company , so it is concluded that the manager must invoke corrective left in this audit to improve internal controls and balances present reasonable and reliable .